Encouragement of Class Magnitude on Student Triumph in Erudition of English Language - Onojah, Adenike Aderogba; Onojah, Amos Ochayi; Jayeosimi, Doctor (Universitas Pendidikan Ganesha, 2023)
The environment which students engage in academic activities need to be reviewed to be up to the standard which students learning would not be jeopardized. Class size determines the number of students in a particular class. This study aims to analyze the influence of class size on student success in learning of English language and the relationship that existed between class size and their students’ academic performance in English Language. This study was an experimental study and harness if students’ achievement in English language correlates with their teachers’ quality. 200 English language students were sampled across schools. The statistical analysis used in the study was the mean, standard deviation and PPMC. The findings established that there was significant influence of class size on student success in learning of English language. The study concluded that the larger the number of students in class, the better the academic success of students in English language. It was however recommended that an average class size as recommended by the National Education scheme/board Commission be adhered to in Nigerian schools.